PENERAPAN PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN MATEMATIKA UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SMA - Rahmadonna, Sisca (MAJALAH ILMIAH PEMBELAJARAN, 2011)
The purpose of this research is to find out about: 1) How Math subject for the eleventh grade science class is taught using contextual learning approach; and 2) Whether contextual learning approach can improve student's motivation in learning the subject. This is an action research using several learning methods such as group discussion and presentation. The data is gathered from observation, interview, questionnaire, test and documentation. From this research we find that contextual learning can be applied for the eleventh grade science class using the seven component of contextual learning approach: constructivism (Constructivism), ask (Questioning), find (Inquiry), community learning (Learning Community), modeling (modeling), reflection (Reflection) and assessment of the actual (Authentic Assessment). The research shows improvement in student's learning motivation – the improvement after the first cycle is categorized as medium and after the second cycle is high, in which all students' test result is satisfactory. From this research, we conclude that contextual learning approach, when implemented correctly, can improve students' motivation in learning math subject.